Neuromatous Regeneration as a Nerve Response After Catheter-Based Renal Denervation Therapy in a Large Animal Model. (May 2015) - Rousselle, Serge D.; Brants, Irena K.; Sakaoka, Atsushi; Hubbard, Brad; Jackson, Nicolette D.; Wicks, Joan R.; Dillon, Krista N.; Naiche, L.A.; Hart, Randy; Garza, Javier A.; Tellez, Armando
<x xml:space="preserve">Abstract</x> Background— Renal denervation (RDN) emerged as a therapeutic option for resistant hypertension. Nerve regrowth after RDN has been questioned. We aimed to characterize the nerve response after RDN. Methods and Results— Swine underwent bilateral RDN and were followed up for 7, 30, and 90 days and evaluated with S100 (Schwann cell), tyrosine hydroxylase (TH; efferent nerves), and growth-associated protein 43 (neurite regeneration) markers. At 7 days, nerve changes consisted of necrosis associated with perineurial fibrosis and distal atrophy with inflammation. At 30 days changes were substituted by healing changes (ie, fibrosis). This response progressed through 90 days resulting in prominent neuroma formation. Immunohistochemistry at 7 days: TH staining was strongly decreased in treated nerves. Early regenerative attempts were observed with strongly TH and growth-associated protein 43 positive and weak S100 disorganized nerve sprouts within the thickened perineurium. Distal atrophic nerves show weak staining for all 3 markers. At 30 days, affected nerves show a weak TH and S100 staining. Evident growth-associated protein 43+ disorganized neuromatous tangles in the thickened perineurium of severed nerves were observed. At 90 days, some TH expression was observed together with prominent S100+ and growth-associated protein 43+ neuromatous tangles with disorganized architecture. The potential for regenerative activity is unlikely based on the disrupted architecture of these neuromatous tangles at the radiofrequency lesion sites. Conclusions— This study is the first documentation that a progressive regenerative response occurs as early as 7 days after RDN, resulting in a poorly organized neuromatous regeneration. This finding is of paramount importance to further establish the potential functional significance of a regeneration after RDN.